Metagenomes from Coastal Marine Sediments Give Insights into the Ecological Role and Cellular Features of Loki- and Thorarchaeota - Lokeshwaran Manoharan (American Society for Microbiology, 2019)
ABSTRACT The genomes of Asgard Archaea, a novel archaeal proposed superphylum, share an enriched repertoire of eukaryotic signature genes and thus promise to provide insights into early eukaryote evolution. However, the distribution, metabolisms, cellular structures, and ecology of the members within this superphylum are not well understood. Here we provide a meta-analysis of the environmental distribution of the Asgard archaea, based on available 16S rRNA gene sequences. Metagenome sequencing of samples from a salt-crusted lagoon on the Baja California Peninsula of Mexico allowed the assembly of a new Thorarchaeota and three Lokiarchaeota genomes. Comparative analyses of all known Lokiarchaeota and Thorarchaeota genomes revealed overlapping genome content, including central carbon metabolism. Members of both groups contained putative reductive dehalogenase genes, suggesting that these organisms might be able to metabolize halogenated organic compounds. Unlike the first report on Lokiarchaeota, we identified genes encoding glycerol-1-phosphate dehydrogenase in all Loki- and Thorarchaeota genomes, suggesting that these organisms are able to synthesize bona fide archaeal lipids with their characteristic glycerol stereochemistry. IMPORTANCE Microorganisms of the superphylum Asgard Archaea are considered to be the closest living prokaryotic relatives of eukaryotes (including plants and animals) and thus promise to give insights into the early evolution of more complex life forms. However, very little is known about their biology as none of the organisms has yet been cultivated in the laboratory. Here we report on the ecological distribution of Asgard Archaea and on four newly sequenced genomes of the Lokiarchaeota and Thorarchaeota lineages that give insight into possible metabolic features that might eventually help to identify these enigmatic groups of archaea in the environment and to culture them.